Penerapan Model Problem Based Learning (PBL) Untuk Meningkatkan Aktivitas dan Pemahaman Konsep Matematika Siswa SMK Nurul Islam Sekarbela - Fina Sari Kamaliah; I Ketut Sukarma; Masjudin Masjudin (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
This study aims to describe the process of applying the Problem Based Learning (PBL) model to improve the activity and understanding of mathematical concepts of SMK Nurul Islam Sekarbela students. This type of research is Classroom Action Research (PTK) which consists of 4 stages, namely planning, implementation, observation and reflection. This research was conducted in two cycles. The subjects in this study were X DKV class students with a total of 10 students. The instruments used were observation sheets and test sheets. The results of Cycle I research show that students' Learning Activities are in the Moderately Active criteria with a percentage of 67% and students' Mathematics Concept Understanding is in the High category with a percentage of 75.32%. Furthermore, in Cycle II there was an increase in student learning activities to be in the Active criteria with a percentage of 78% and students' understanding of mathematical concepts also increased to be in the Very High category with a percentage of 86.64%. Thus it can be concluded that through the application of the Problem Based Learning (PBL) model can increase the activity and understanding of mathematical concepts of SMK Nurul Islam Sekarbela students.